Antimüllerian hormone levels decrease in women using combined contraception independently of administration route - Kallio, Sanna; Puurunen, Johanna; Ruokonen, Aimo; Vaskivuo, Tommi; Piltonen, Terhi; Tapanainen, Juha S (Fertility and sterility, 2013)
To compare the effects of continuous use of oral (OC), transdermal, and vaginal combined contraceptives on the pituitary-ovarian axis and inhibition of follicular development. Spin-off study of a prospective, randomized trial. University clinic. Forty-two of 54 healthy women completed the study. Treatment with combined OCs (ethinyl E2 [EE] and desogestrel), transdermal patches (EE and norelgestromin), or vaginal rings (EE and etonogestrel) for 9 weeks continuously. Blood sampling was performed before and at 5 and 9 weeks of treatment. Changes in serum hormone levels induced by combined contraceptives. Serum antimüllerian hormone (AMH), FSH, inhibin B, LH, and E2 levels had decreased significantly in all study groups after 9 weeks of treatment. Significant declines were already detected after 5 weeks' use of combined contraceptives with regard to all hormone levels apart from those of serum AMH, where the decrease between baseline and 5 weeks was only moderate. Between groups, serum levels of AMH, inhibin B, LH, and E2 were comparable at baseline and after 5 and 9 weeks of treatment. The decrease of serum AMH levels during the use of all combined contraceptives indicates that folliculogenesis is arrested independently of administration route. NCT01087879.